What Can We Learn From Assisted Bicycle Training in a Girl With Dystrophinopathy? A Case Study. (April 2015) - Huijben, Jilske; Jansen, Merel; Ginjaar, Ieke B; Lammens, Martin; van Putten, Maaike; van Alfen, Nens; de Groot, Imelda JM
In this case study, a 9-year-old ambulatory girl with dystrophinopathy due to a mosaic translocation mutation participated in dynamic training. Because the role of exercise is unclear in both boys and girls with dystrophinopathy, a recently developed assisted bicycle training regimen was evaluated for its feasibility and effectiveness in this girl. The girl trained at home, first 15 minutes with her legs and then 15 minutes with her arms, 5 times a week, for 24 weeks. This case study showed that the training was feasible and safe. In addition, we found that no physical deterioration occurred during the training period: the Motor Function Measure and the Assisted 6-Minute Cycling Test results remained stable. Slight improvements in quantitative muscle ultrasound intensity were found, indicating less fatty infiltration in the muscles. These results suggest that physical training could be beneficial in females with dystrophinopathy who express low levels of dystrophin.